Design Considerations of Series-Connected Devices Based LLC Converter - Dongkwan Yoon; Sungmin Lee; Younghoon Cho (Energies, 2020)
This paper describes the design of a Series-Connected Device based on a fixed−frequency LLC resonant converter (SCDLLC). Isolation of the dc-dc converter like the LLC resonant converter is used for the stability of the high voltage system such as a solid-state-transformer (SST). The series-connected devices driving method is one of the methods applicable to a high voltage system. When driving series-connected devices, an auxiliary circuit for voltage balancing between series-connected devices is required, which can be simply implemented using a passive element. In this paper, LLC converter design with balancing circuits configured in parallel with a device is provided, and both the simulations and experiments were performed.